Mathematical functions for the prediction of growth in Indian dromedary genotypes - Mehta, S C; Bapna, D L; Bhure, S K (The Indian Journal of Animal Sciences, 2011)
Growth of Bikaneri, Jaisalmeri, Kachchhi and Arabcross (Arab×Bikaneri) camels from birth to 20 years of age was analyzed for the year 1984 to 2005. The average annual body weights in the Indian dromedary were recorded as 37.1±0.3, 208.6±2.2, 269.1±3.5, 346.1±4.3, 403.4±4.3, 460.2±6.6, 510.2±7.4, 541.8±7.7, 569.8±8.3, 576.0±9.0, 575.9±9.4, 585.7±9.8, 569.8±9.6, 571.0±11.2, 566.5±11.2, 569.7±12.4, 547.6±12.3, 576.2±13.9, 569.8±16.6, 558.9±16.6 and 548.0±18.4 kg, respectively from birth to 20 years of age. The male sex was differentiated from the female sex at 24 months of age but the genetic groups were nonsignificantly different from each other except the Arabcross camels at some stages. It was observed that the camels attain their adult weight at 8 years of age but the growth phase continues up to 11 years of age. The linear, quadratic, cubic, exponential and Gompertz functions were derived to explain the ageweight relationship in Indian dromedary genotypes and the respective R2 values were 0.661, 0.964, 0.994, 0.45 and 0.967. It is quite evident from the analysis that the cubic function explains the growth of camel for the entire life time to the extent of 99.4%, hence the cubic equation Y = 73.2592 + 9.9072X– 0.0631X2 + 0.000128 X3 can be utilized for the estimation of body weight of camels of different sexes and genetic groups.